Виробництво та структура пористого заліза з контрольованою пористістю та розміром пор - Руденко, Наталія Олександрівна (НТУ "ХПІ", 2017)
Розглянуто технологію виготовлення високопористих матеріалів на основі порошку заліза. Для створення високої пористості застосовували порошки бікарбонату амонію, хлориду натрія, гідрокарбонату натрія. Вивчено закономірності пресування порошкових сумішей, спікання пресовок. Для отримання якісних високопористих виробів рекомендується застосовувати бікарбонат амонію. Встановлено вплив тиску пресування і складу сумішей на основі заліза та бікарбонату амонію на мікроструктуру пористих зразків. Після спікання відносна пористість зразків незначно зменшується, бо пористість визначається порами, що утворюються після видалення пороутворювача.

The powder metallurgy route for manufacturing of highly porous iron based materials was considered. To increase porosity the powders of ammonium, bicarbonate sodium chloride and sodium bicarbonate were mixed with iron powder. The mixtures of basic iron powder and pore-forming materials were compacted and sintered. Pore-formers were removed during or after sintering leaving additional pores. The influence of mixture composition on compaction, amount of pore-former on sintering and microstructure of sintered parts were studied. Ammonium bicarbonate suits to this requirement and can be recommended for usage at production of high quality porous parts. The influence of compaction pressure and mixture composition on the microstructure of porous samples is provided. After sintering the relative porosity of the samples decreases insufficient, because porosity is determined by large pores formed after pore-former removal. With increase of pore-former content in the mixture the porosity of sintered products increases and with increase of compaction pressure their porosity slightly decreases.
Processing and structure of porous iron with controlled porosity and pore size
Keywords: високопористі матеріали; пороутворювач; ущільнення; усадка; мікроструктура; спечені вироби; highly porous materials; pore-former; densification; sintered parts